A NEED ANALYSIS IN LEARNING ENGLISH FOR LAW FACULTY STUDENTS AT IISBUD SAMAWA REA - Samsudin Samsudin; Sukarismanti Sukarismanti (p-ISSN 2356-0576, 2020)
Abstract: Needs analysis is necessary for the institutions to design or develop the English curriculum to find out a set of competencies needed by the students. Need analysis is to find specific needs for the students in the institution may direct the institution to an English program called English for Specific Purposes (ESP). This study was aimed to find out (1) difficul skills are faced by students of law faculty in mastering English Language, and (2) the basic skills and materials that are considered necessary and unnecessary to be taught to law faculty students in mastering English relating to law subject. Analysis of English language needs is done by giving questionnaires to students to answer, those questions concerning which field of English they are very proficient (speaking, listening, reading and writing) and which areas of English they find it difficult to learn, and choose what lessons they think are necessary which have not been provided in the current syllabus. The result showed that most of students regard to speaking, listening are the most difficult skill of English than other. Then the skill should be taught in English subject is speaking. Speaking skill is the most urgent to teach than other. Addition to, the English materials which related to law are considered necessary to taught is law vocabulary, meeting people, custom law in Indonesia, general election practice using English, and games relating to English law. From this research, it is expected that students can improve their English language skills in Law.   Keywords: Need Analysis, English, Law Faculty, ESP